CLOUD COMPUTING IN BANKING SYSTEM - Saffela, Nurika Indah; Miranti, Namira Putri; Shalihah, Dian Karunia (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
This article examines the cloud in the banking sector by providing significant operational efficiency, cost savings, and flexibility. Substantial synergies exist in controlling operational risks when these technologies are used together. This study uses a literature review of relevant articles from 2013 to 2024. We conclude that the cloud is appropriate because the agility and flexibility in cloud services allow banks to scale their operations quickly, adapt to market changes, and respond to customer needs more effectively. Enhanced Customer Experience by leveraging cloud technology can offer more innovative and customer-centric services, increasing customer satisfaction and loyalty. Overall, the results show that the cloud is a transformative force in the banking sector, enabling institutions to navigate the complexities of a rapidly evolving financial landscape. With proper planning and a deep understanding of the risks and benefits, banks can leverage this technology to achieve their business goals.